HUBUNGAN KONSEP DIRI DENGAN SELF-EFFICACY PADA SISWA KELAS X SMK KARYA JAYA TANJUNG MORAWA - Khofifah Indah Ayu; Nurul Azmi Saragih (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the relationship between self-concept and self-efficacy of class X students at SMK Karya Jaya Tanjung Morawa. The hypothesis proposed is that there is a positive and significant relationship between self-concept and self-efficacy in class X students at SMK Karya Jaya Tanjung Morawa. The research method used is descriptive quantitative approach with the type of research used is descriptive correlational research. Determination of the sample of this study was a population study of 118. The population in this study was 30 people to obtain the necessary data, so in this study the researchers used data collection tools in the form of questionnaires and documentation. Based on the results of research at SMK Karya Jaya Tanjung Morawa using the calculation of the product moment correlation of the two variables Self-Concept (X) and Self-Efficacy (Y). The level of self-concept of students is 93.93% in the high category, the level of self-efficacy is 81.57% in the high category, the level of the relationship between self-concept and self-efficacy is 0.331> 0.284. This shows that there is a relationship between self-concept and self-efficacy in students.